Reconstructing Renewable Energy: Making Wind and Solar Power Dispatchable, Reliable and Efficient - Prentis, Eric L. (International Journal of Energy Economics and Policy, 2016)
This paper is important because it explains how to create a grid-scale energy storage system (ESS) that makes, for the first time, wind and solar renewable energy—dispatchable, reliable and efficient. Existing and recent discoveries in battery technology are analyzed, with the most appropriate recommended for use in the new ESS. Additionally, an innovative time-shifting ESS design approach is presented that decouples electricity production from use, considerably improving total wind and solar power peak average capacity contribution values. This minimizes the need for expensive standby natural-gas combustion turbine peaker plants—thereby decreasing costs by 75%. Furthermore, this advanced ESS improves performance by making the interconnection grid more reliable and better able to handle changing customer demands, relieves transmission congestion, and decreases unscheduled power outages—and also provides ancillary services; thereby improving system-wide benefits by 30%-to-40%, further reducing effective ESS costs, perhaps to zero. Keywords: Renewable Energy, Efficiency, Dispatchable, Grid-Scale Energy Storage System JEL Classifications: G31; G38; H44; K23